Effects of L-tryptophan and L-methionine on activity in the rat. - Taylor, M (1976)
1 The effects of an intraperitoneal dose of 20 mg/kg L-tryptophan and doses of 100 and 150 mg/kg of L-methionine were investigated on activity in the rat. 2 Activity was measured by a time sampling behaviour categorization procedure, and began 15 min after compound administration, lasting for a total of one hour. 3 Total active behaviour in the first half hour was reduced after 20 mg/kg tryptophan, 100 or 150 mg/kg methionine. Only 20 mg/kg tryptophan led to a significant reduction in active behaviour during the second half hour. 4 Administration of 100 mg/kg methionine plus 20 mg/kg tryptophan, and 150 mg/kg methionine plus 20 mg/kg tryptophan had no discernible effect on activity. 5 The results draw attention to the role of another amino acid in the modification of the behavioural effects of tryptophan.